Kidnapped - Stevenson, Robert Louis; Robert Louis Stevenson (New York Random House, 1994)
an adventure novel following 17-year-old David Balfour, who is cheated out of his inheritance and kidnapped by his miserly uncle Ebenezer to be sold into slavery.
Keywords: The story is set in 18th-century Scotland; the power of loyalty, the strength of friendship